Observations on particle size/spacing relationships and phase equilibria in the Cu-Ni-Cr system - Findik, Fehim (Springer Science and Business Media LLC, 1993)
The development of increased strength in Cu-Ni-Cr alloys, compared to binary Cu-Ni alloys, depends upon heat treatment. Alloys have compositions which permit them to be solution treated at elevated temperature and then aged at a lower temperature, in a two-phase field, to produce hardening. The decomposition into two phases may occur by nucleation and growth or by a spinodal reaction, depending on the alloy composition and the heat-treatment temperature. In this study, the relationship between particle size and wavelength (interparticle spacing) was studied in some Cu-Ni-Cr spinodal alloys and it was found that the wavelength was directly proportional to the particle size. Also, the Cu-Ni-Cr ternary diagram at the 930 °C isothermal section was similar to that obtained by Meijering et al.